Synthesis, characterization and antibacterial studies of Co(ii), ni(ii) and zn(ii) complexes of schiff base derived From 4-methoxy aniline - S MINI; S DARSANA (International Journal of Pharma and Bio Sciences, 2017)
Three new transition metal complexes have been prepared using the Schiff base furan-2-ylmethylene-(4-methoxy-phenyl)-amine. These complexes were characterized by various physico- chemical analyses such as elemental analyses, metal estimation, anion estimation, conductivity measurements and magnetic moment measurements. They were also confirmed by spectral analyses like FTIR, UV-Visible, NMR and Mass. The result shows that the ligand is acting in a bidentate manner through its ‘N’ and ‘O’ donor atoms .The ligand and the complexes were screened for antibacterial study against Escherichia coli in different concentrations.